UJI KINERJA ALAT PENYULINGAN NIRA AREN MENJADI BIOETANOL DI KELOMPOK TANI HUTAN TAYAPU DESA TALAWAAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Solar, Trivano; Wenur, Frans; Lengkey, Lady C. Ch. E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2021)
This study aims to determine the performance of the distillation tool aid by the North Sulawesi Forestry Service for the Hutan Tayapu Farmer Group consisting of temperature conditions in the distillation process, alcohol content, distillation rate, product yield, and energy consumption as well as to calculate the energy efficiency of the distillation tool. This research uses experimental methods. Data is presented in tables and graphs, then computed and analyzed descriptively. Bioethanol production is carried out 2 times each using 100 liters of palm sap. The results showed that the distillation process took place at a temperature ranging from 29.2 °C to 100.9 °C. The obtained alcohol content ranged from 26% to 64%, with energy efficiency of 4.96% for the appliance, and the distillation rate in the range of 1.87-8.40 liter/hour.